Grey zone in - greenwash out: A review of greenwashing research and implications for the voluntary-mandatory transition of CSR - Lucia Gatti; Peter Seele; Lars Rademacher (International Journal of Corporate Social Responsibility (JCSR), 2019)
As public concern over greenwashing has grown in the last two decades, academic research has increased correspondingly, and there is now a substantial body of research addressing issues related to greenwashing. In this paper, we therefore review and analyze greenwashing research, to provide an evaluation of trends and progress in the field and a synthesis of the empirical and conceptual results presented in existing studies. Our main finding leading to our theory contribution is the criticism raised in greenwashing research that the entirely voluntary CSR (Corporate Social Responsibility) approach facilitates the diffusion of greenwashing. The voluntary idea of CSR is still prevalent in the CSR literature and appears to be a grey-zone that creates space for misleading 'green' communication. Consequently, we propose that greenwashing could be better prevented with a combination of voluntary and mandatory aspects. The new paradigm should promote creative and effective corporate CSR initiatives, while at the same time design the limits and the rules for their accomplishments and communication, as firms would risk breaching legislation when overstretching CSR messages.
Keywords: 650; Greenwashing; Corporate social responsibility; CSR communication; Mandatory CSR